2014
DOI: 10.1080/09168451.2014.877819
|View full text |Cite
|
Sign up to set email alerts
|

Development of hypoallergenic galacto-oligosaccharides on the basis of allergen analysis

Abstract: Galacto-oligosaccharides (GOSs) are recognized as prebiotics beneficial to human health through their abilities to modulate gut microbiota. On the other hand, it has been reported that immediate allergic reactions are caused by a GOS product (Bc-GOS) produced by treating lactose with β-galactosidase derived from Bacillus circulans. The objective of this study was to create a safer GOS product that is less likely to cause GOS-induced allergy (GOS-AL). First, we identified two derivatives of tetrasaccharide suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 50 publications
0
26
1
1
Order By: Relevance
“…Twenty years later, allergic reactions were noted after consumption of GOS‐supplemented milk formula in 16 Vietnamese and 5 Singaporean cow's milk–tolerant children . During the same period, increasing allergic reactions after consumption of GOS‐supplemented lactic acid beverages were also reported in Japan, some of which developed anaphylaxis presenting with respiratory distress . Chiang et al demonstrated that all five patients were sensitized to short‐chain (sc) GOS and fractions of scGOS containing 3 sugar units or greater but not to cow's milk or long‐chain fructo‐oligosaccharides.…”
Section: Anaphylaxis Triggers—east Vs Westmentioning
confidence: 98%
See 1 more Smart Citation
“…Twenty years later, allergic reactions were noted after consumption of GOS‐supplemented milk formula in 16 Vietnamese and 5 Singaporean cow's milk–tolerant children . During the same period, increasing allergic reactions after consumption of GOS‐supplemented lactic acid beverages were also reported in Japan, some of which developed anaphylaxis presenting with respiratory distress . Chiang et al demonstrated that all five patients were sensitized to short‐chain (sc) GOS and fractions of scGOS containing 3 sugar units or greater but not to cow's milk or long‐chain fructo‐oligosaccharides.…”
Section: Anaphylaxis Triggers—east Vs Westmentioning
confidence: 98%
“…45,46 During the same period, increasing allergic reactions after consumption of GOS-supplemented lactic acid beverages were also reported in Japan, some of which developed anaphylaxis presenting with respiratory distress. 47 Chiang et al 45 demonstrated that all five patients were sensitized to short-chain (sc) GOS and fractions of scGOS containing 3 sugar units or greater but not to cow's milk or long-chain fructo-oligosaccharides. The prevalence of GOS allergy has now been estimated to be around 3.6% in the atopic Singaporean population.…”
Section: Galacto-oligosaccharide Allergy First Came To Attention Inmentioning
confidence: 99%
“…They are nondigestible oligosaccharides that, when ingested, function as prebiotics. Although available in consumer products globally, reports of allergic reactions and anaphylaxis to GOS have been confined to the Asian region – Japan , Singapore , Malaysia and Thailand (unpublished), and likely Vietnam . This is an unusual allergy as the trigger is a pure carbohydrate .…”
Section: Allergic Reactions To Vgos Challengementioning
confidence: 99%
“…This is an unusual allergy as the trigger is a pure carbohydrate . GOS, being a small molecule, is unlikely to cross‐link IgE on mast cells, but it has been shown in animal studies to be immunogenic when coupled with carrier proteins ; there is suggestion that in patients with GOS allergy, this protein component may be one found on the cell surface . The five reported cases from Singapore were above 5 years old, atopic and tolerant to cow's milk.…”
Section: Allergic Reactions To Vgos Challengementioning
confidence: 99%
“…GOS are produced by lactose transglycosylation by b-galactosidase, which generates a mixture of short-chain oligosaccharides (2-6 DP, >95 %) with galactosyllactose (GL) isomers (3¢-GL, Galb1-3Galb1-4Glc; 4¢-GL, Galb1-4Galb1-4Glc; 6¢-GL, Galb1-6Galb1-4Glc) as the main components (Fig. S1, available with the online Supplementary Material) [21,22].…”
Section: Introductionmentioning
confidence: 99%